Profile of Physics Creative Thinking Skills for High School Students in The 21st Century - Nazhifah, Nauratun; Wiyono, Ketang; Ismet; Azairok , Muniatuz (Universitas Nurul Huda, 2023)
Creative thinking is one of the 21st-century skills that every individual should possess. These skills facilitate the individual in realizing the imagination, providing an opportunity to think and express ideas. So knowing the profile of creative thinking skills is considered very important. This study aims to analyze creative thinking skills in learning activities teaching physics subjects on the topic of temperature and heat. This type of research is quantitative descriptive research with test methods. Class XI students of one of the public high schools in Central Bangka became the population in this study. The sample in this study was 64 students who were selected by purposive sampling. Data were collected using Creative Thinking Skills Physics SMA (PhysCreTHOTS). The results showed students' creative thinking skills on temperature and heat material were at a percentage of 54.40% with sufficient categories. And there are no students who are in the category of very good and very less. Then students' creative thinking skills based on creative thinking indicators are all classified as sufficient with a percentage of 57.81% (fluency), 45.57% (flexibility), 56.25% (originality), and 58.59% (elaboration). The results of this discovery can be used as empirical evidence and references that in the implementation of physics learning students' creative thinking skills still need to be improved.